Characteristics of Dentists Providing Dental Care to Publicly Insured Patients - Nadereh Pourat, PhD; Dylan H. Roby, PhD; Roberta Wyn, PhD; Marvin Marcus, DDS (Blackwell Synergy, 2007)
This study aims to identify the practice and patient care characteristics of dentists who provide care to publicly insured patients, beyond currently available existing information, which is typically limited to demographics of such dentists.